Buerger Allen exercise in patients with diabetes mellitus type II to improve peripheral blood circulation and blood glucose levels - Yammar, Yammar; Fatmawati, Fatmawati; Nurfadilah, Nurfadillah (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Type 2 diabetes mellitus (T2DM) is a prevalent chronic metabolic disorder among the elderly, characterized by elevated blood glucose levels and a high risk of complications, including impaired peripheral circulation. Older adults are particularly susceptible due to physiological decline and reduced physical activity. The Buerger Allen exercise is known to enhance peripheral blood flow and assist in controlling blood glucose levels. Purpose: To examine the effect of Buerger Allen exercises on peripheral circulation among elderly individuals with type 2 diabetes mellitus. Method: A quantitative quasi-experimental design with a one-group pretest–posttest approach was applied. The intervention involved performing Buerger Allen exercises three times per week for two weeks, with each session lasting 17 minutes. The study included 10 elderly participants residing in Atakkae Village, with data collected at the Salewangeng Community Health Center. A total sampling technique was employed, resulting in a sample size of 10 respondents. Results: The mean Ankle Brachial Index (ABI) increased from 0.94 mmHg (pretest) to 0.99 mmHg (posttest), indicating improved peripheral circulation. Additionally, the average random blood glucose (RBG) level decreased from 323.6 mg/dL to 308.3 mg/dL after the intervention. Statistical analysis yielded a p-value < 0.05 for both parameters, signifying a significant effect of the Buerger Allen exercise on peripheral blood circulation and glucose reduction. Conclusion: Buerger Allen exercises are effective in enhancing peripheral blood circulation and lowering blood glucose levels among elderly patients with type 2 diabetes mellitus.